MAGNETIC PROPERTIES OF ALLUVIAL SOILS CONTAMINATED WITH LEAD, ZINC AND CADMIUM - Petrovsky E.; Kapicka A.; Jordanova N. (My University, 2001)
Several proxy methods have been used recently to outline increased levels of pollution. One of them is based on measurements of the concentration of (ferri)magnetic minerals of anthropogenic origin. This method has been used recently in the mapping of both polluted and unpolluted areas. In order to validate this method, a more detailed study of links between magnetic parameters characterising the physical shape of magnetic minerals and concentrations of heavy metals is needed. In this study, we analysed the magnetic characteristics of alluvial soils, formed as a result of several breakdowns of wet deposit sink of ashes from a lead ore smelter. The soils were previously analysed for concentration of lead, zinc and cadmium. Our results show that in this case of a shared source of heavy metals and magnetic minerals, simple measurements of magnetic susceptibility discriminate well between polluted and clean areas. In addition, the concentration pattern agrees with the concentrations of the heavy metals studied in deeper soil layers that were not affected by post-depositional changes due to climate and remediation efforts.
Keywords: MAGNETIC PROPERTIES; ALLUVIAL SOIL; HEAVY METALS